1988
DOI: 10.1128/mcb.8.7.2884
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleoproteins package 700 nucleotides of pre-mRNA into a repeating array of regular particles.

Abstract: An assay for the in vitro assembly of HeLa cell 40S nuclear ribonucleoprotein particles (hnRNP particles) has been developed. The substrates were single-stranded nucleic acid polymers of defined length and sequence prepared in vitro and the six major core particle proteins from isolated 40S hnRNP. The fidelity of in vitro assembly was evaluated on various physical parameters, including sedimentation, salt dissociation, polypeptide stoichiometry, UV-activated protein-RNA cross-linking, and overall morphology. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 52 publications
2
85
1
Order By: Relevance
“…Surprisingly, an immunologically related protein of approximately the same molecular mass as hnRNP F was detected in the yeast S. cerevisiae. hnRNP proteins are commonly conserved among vertebrates, however few related proteins have been identified in yeast (1,29 Although it has been demonstrated that many hnRNP proteins display RNA sequence binding preferences, all of the previously characterized proteins appear to also bind nucleic acids in an apparently sequence independent manner (2,41,42). One unique feature of hnRNP F and hnRNP H is that poly(rG) is the only nucleic acid that they have been found to bind to in vitro (2,28).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, an immunologically related protein of approximately the same molecular mass as hnRNP F was detected in the yeast S. cerevisiae. hnRNP proteins are commonly conserved among vertebrates, however few related proteins have been identified in yeast (1,29 Although it has been demonstrated that many hnRNP proteins display RNA sequence binding preferences, all of the previously characterized proteins appear to also bind nucleic acids in an apparently sequence independent manner (2,41,42). One unique feature of hnRNP F and hnRNP H is that poly(rG) is the only nucleic acid that they have been found to bind to in vitro (2,28).…”
Section: Resultsmentioning
confidence: 99%
“…The equilibrium binding of hnRNP Al to single-stranded polyaucleotides is cooperative and shows limited base specificity (28). In vitro reconstitution studies with hnRNP core proteins also show a lack of sequence specificity (29). However, the contacts ofhnRNP Al with pre-mRNA are sensitive to the presence of additional factors in nuclear extracts (30), and specific binding of hRNP Al …”
Section: Discussionmentioning
confidence: 99%
“…However, this protein binds to poly(U)-Sepharose in the presence of 2 M KC1, whereas PTB elutes from this resin at 750 mM KC1, suggesting that these proteins are distinct. Moreover, hnRNP proteins are generally thought to bind RNA nonspecifically (Conway et al 1988), much the way histones bind DNA. If this is the case, PTB does not fit the description of an hnRNP protein.…”
Section: Is Ptb An Hnrnp Protein?mentioning
confidence: 99%